Recent sedimentation rates using 210Pb and 137Cs vertical profiles of core sediments at the Gulf of Corinth, Litochoro Coast and Marmara Sea - Papageorgiou, D.; Eleftheriou, G.; Patiris, D. L.; Sakellariou, D.; Tsabaris, C.; Kokkoris, M.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2020)
In this work, core sediment samples up to 50 cm have been collected from three different marine environments; Gulf of Corinth, Gulf of Thermaikos, specifically from Litochoro Coast and Lake Uluabat from the wider region of Black Sea. Natural (210Pb) and anthropogenic (137Cs) radionuclides in the samples were measured using an HPGe detector, calibrated for sediments geometry. The vertical distribution of 137Cs and 210Pb was used to determine the sedimentation rate. The results were 0.56 cm/year for the Gulf of Corinth and 0.54 cm/year for the coast of Litochoro. In the case of the lake Uluabat the sedimentation rate was 0.41 cm/year.